2018
DOI: 10.1002/gcc.22541
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of chromosomal imbalances, gene mutations, and BAP1 expression in uveal melanoma

Abstract: Uveal melanoma (UM) exhibits recurring chromosomal abnormalities and gene driver mutations, which are related to tumor evolution/progression. Almost half of the patients with UM develop distant metastases, predominantly to the liver, and so far there are no effective adjuvant therapies. An accurate UM genetic profile could assess the individual patient's metastatic risk, and provide the basis to determine an individualized targeted therapeutic strategy for each UM patient. To investigate the presence of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 62 publications
(154 reference statements)
3
13
0
Order By: Relevance
“…These gene mutations were not identified in the cutaneous melanoma, which was consistent with the literature 31. Mutations in GNAQ (50%) and GNA11 (44%) are early events that promote cell proliferation, suggesting that activated G-protein signaling plays a crucial role in early uveal melanoma development 12. In addition to mutated genes mentioned above, uveal melanoma also harbored additional SF3B1 (22%), EIF1AX (12%), COL14A1 (4%), CYSLTR2 (4%), MACF1 (4%), MUC16 (4%) and MYOF (4%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These gene mutations were not identified in the cutaneous melanoma, which was consistent with the literature 31. Mutations in GNAQ (50%) and GNA11 (44%) are early events that promote cell proliferation, suggesting that activated G-protein signaling plays a crucial role in early uveal melanoma development 12. In addition to mutated genes mentioned above, uveal melanoma also harbored additional SF3B1 (22%), EIF1AX (12%), COL14A1 (4%), CYSLTR2 (4%), MACF1 (4%), MUC16 (4%) and MYOF (4%).…”
Section: Discussionsupporting
confidence: 87%
“…BAP1 mutations are related to metastasis and EIF1AX mutations are associated with favorable metastatic-free survival 7-10. Uveal melanoma patients with chromosome 3 copy number loss are associated with a high risk of metastasis and a poor outcome 11, 12. It was reported that UM tumor progression typically displays chromosomal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monosomy 3 tumors from both groups C and D showed gain of the entire 8q arm in nearly all samples as reported previously in TCGA cohort (20). Patients with monosomy 3, 8p loss, and 8q gain had lower overall survival (OS) as described elsewhere (30)(31)(32)(33)(34)(35). When examined independently, chromosomal alterations associated with metastatic disease were loss of 3p (P ¼ 2.29 Â 10 À8 ), loss of 3q (P ¼ 2.95 Â 10 À7 ), loss of 6q (P ¼ 0.0246), gain of 8q (P ¼ 0.0001), and loss of…”
Section: Broad Copy Number Alterations In Uveal Melanomasupporting
confidence: 78%
“…Dysregulation of BAP1 exclusively occurs in UM progression and exhibits a strong correlation to UM metastasis. Recently, Patrone et al 6 revealed that loss of BAP1 protein was significantly associated with prolonged progression-free survival in patients with UM. Moore et al 7 demonstrated that RasGRP3 is a potential target and it is specifically required for Ras activation and tumorigenesis of UM cells.…”
Section: Introductionmentioning
confidence: 99%